Use of microbial additives in apiculture - Milián, Grethel; Martínez, Marlene M.; Rondón, Ana J.; Rodríguez, Marlén (Cuban Journal of Agricultural Science, 2023)
A compilation of the apiculture history, main diseases of bees, ways for their control and the use of probiotics in the care of these insects is show. Probiotics are live microorganisms that when they are intake in adequate amounts they confer benefits to the host health. Among the most bacteria used with this purpose, are those from Bacillus genus and their species subtilis, which are highlighted due to their capacity of founded the microbial balance in the gastrointestinal tract and modulate the immune system. This performance is favorable for the processes of digestion and nutrients absorption, in addition decrease the incidence of infectious diseases. If there is evidence of the probiotic effect, In vitro and in vivo, of this species in a group of animals of zoothecnical interest, few of their use in apiculture is know. Key words: bees, Bacillus subtilis, probiotics